2021
DOI: 10.1016/j.crfs.2021.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The bioactive, antioxidant, antibacterial, and physicochemical properties of a range of commercially available Australian honeys

Abstract: Honey is a supersaturated sugar solution produced from plant nectar, with its composition influenced by geographic and floral origins, and with several properties contributing to its health-related abilities. This study aimed to determine the bioactive composition, antioxidant characteristics, antibacterial activity, and physicochemical properties of commercial Australian honeys. In total, 42 commercial Australian honeys were selected, and categorised according to front-label descriptions. Honeys were analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 62 publications
2
13
1
2
Order By: Relevance
“…As expected, TPC, DPPH and FRAP showed a very strong positive correlation with each other (r = 0.637 and 0.684, p < 0.001). In the literature, correlations among these three parameters depend on the honey type [ 17 , 81 , 85 ]. These data indicate that the antioxidant activity is mainly attributed to phenolic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, TPC, DPPH and FRAP showed a very strong positive correlation with each other (r = 0.637 and 0.684, p < 0.001). In the literature, correlations among these three parameters depend on the honey type [ 17 , 81 , 85 ]. These data indicate that the antioxidant activity is mainly attributed to phenolic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Bucekova et al ( 61 ) observed that the antibacterial activity of Slovakian commercial honeys against S. aureus is not uniform. Similarly, Hunter et al ( 6 ) established differences in the antibacterial activity of different Australian honeys, depending on the bacterial species. All samples were effective as an inhibitory agent against S. aureus , MIC 50 concentrations ranging from 0.078 to 5.82% (w/v), whereas the lowest concentration to inhibit the growth of P. aeruginosa was 25% (w/v).…”
Section: Discussionmentioning
confidence: 97%
“…Other studies, comparing quality, antioxidant and antibacterial properties of honeys, revealed further connections. Antibacterial activity of the Australian honey samples was associated with the antioxidant characteristic measured by FRAP (Ferric Reducing Antioxidant Power) method, and their phenolic content contributed to both antioxidant and antibacterial effects ( 6 ). Deng et al ( 58 ) compared the biochemical properties, antibacterial and cellular antioxidant activities of the dark colored buckwheat and manuka honeys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The honey with the highest HMF content (432 mg/kg) was also one of the honeys demonstrating a decrease in MGO content when comparing measured versus stated levels, which supports the theory that the honey may have been stored for considerable time. Since few studies have analysed large numbers of manuka/ Leptospermum honeys for physicochemical properties such as pH, sugar content, colour, total phenolics content and antioxidant activity, comparison of the current data to previous studies is limited, however, the available data are broadly similar [ 9 , 32 , 33 ]. Manuka honeys produced very low levels of hydrogen peroxide, which was expected due to the known interference of MGO with the glucose oxidase enzyme [ 34 ].…”
Section: Discussionmentioning
confidence: 99%